EFFECT OF THE HEAT RECOVERY SYSTEM TO THE PERFORMANCE OF AIR HANDLING UNIT OF A SHOPPING CENTRE - Kelasovali, Furkan; Celen, Ali; Kayaci, Nurullah; Dalkilic, Ahmet Selim; Wongwises, Somchai (AMER SOC MECHANICAL ENGINEERS, 2013)
In today's world, the efficient use of energy is very important due to short of energy sources. In order to use energy efficiently, some methods/devices have been developed recently. One of them is heat recovery systems which are used for energy saving in the Heating Ventilating and Air Conditioning applications. Air handling units (AHUs) equipped with heat recovery system can be used applications for energy saving. Not only this paper presents information about rotary heat exchangers which is one of the air to air heat recovery systems but also it investigates their effects to system when they are used in an application. In the study, a shopping centre, which is located in the capital city of Turkey, is taken consideration. The shopping centre has an air handling unit having 54567 m(3)/h fresh air flow rate, 640 kW heating and 41 kW cooling capacity. Calculations are performed for AHU of the shopping centre both equipped with rotary heat exchanger and without rotary heat exchanger. In order to compare performance of AHUs, annual energy saving, initial investment cost, annual operating expenses, payback time and profit parameters are calculated for each month. According to the results, heating battery power in the heating season and cooling battery power in the cooling season is significantly decreased by using heat recovery system and total annual energy saving is calculated as $83,444. Consequently, it is found that the use of rotary heat exchanger improves performance of system in terms of the reduction in required powers and costs.
Keywords: EXCHANGER; Energy & Fuels; Engineering